Effect of the viscosity ratio on the PLA/PA10.10 bioblends morphology and mechanical properties - J. Cailloux; T. Abt; V. Garcia-Masabet; O. Santana; M. Sanchez-Soto; F. Carrasco; M. Ll. Maspoch (eXPRESS Polymer Letters)
PLA bio-blends with a predominantly biosourced PA10.10 in the composition range 10–50 wt% were prepared by melt blending in order to overcome the advanced brittleness of PLA. Due to the inherent immiscibility of the blends, 30 wt% of PA was needed to achieve a brittle-to-ductile transition and a co-continuous morphology was predicted at 58 wt% of PA. The initial enhancement of the PLA rheological behaviour through the environmentally friendly reactive extrusion process yielded a finer and more homogeneous microstructure and hence enhanced the mechanical properties of the bioblends at much lower PA contents. The brittle-to-ductile transition could be achieved with only 10 wt% and co-continuity was observed already at 44 wt% of PA. Results indicate the significant potential of modifying PLA flow behaviour as a promising green manufacturing method toward expanding PLA-based bio-blends applications.